Vitamin E for the Prevention of Chemotherapy-Induced Peripheral Neuropathy: A meta-Analysis - Chen, Jie; Shan, Haili; Yang, Wenjun; Zhang, Jiali; Dai, Haibin; Ye, Ziqi (Frontiers in Pharmacology, 2021)
Background: Vitamin E has been increasingly used to prevent chemotherapy-induced peripheral neuropathy (CIPN) in recent years. However, it is still unclear whether vitamin E can effectively prevent CIPN. Methods: We searched all clinical studies in the Embase, Cochrane Library, Clinicaltrials.gov, and PubMed databases from inception to December 2020. We performed a meta-analysis of 9 randomized controlled trials (RCTs) with 486 patients that compared the vitamin E group with the control group. Outcomes of the study were incidence of all-grade CIPN, incidence of severe CIPN, and the total neuropathy scores (TNS). Random effect models were used to make the meta-analysis results more cautious. Results: Notably, vitamin E significantly reduced the incidence of all-grade CIPN (overall risk ratio (RR) = 0.55, 95% CI: 0.36, 0.85, I2 = 77.3%, p = 0.007), and TNS (overall standard mean difference (SMD) = −0.64, 95% CI: −1.03, −0.25, I2 = 42.7%, p = 0.001). However, the results of the subgroup analysis, which included only double-blind RCTs, suggested that vitamin E did not significantly reduce the incidence of all-grade CIPN (overall RR = 0.52, 95% CI: 0.07, 4.06, I2 = 77.5%, p = 0.531). Moreover, there was no significant difference in the incidence of severe CIPN between these two arms (p = 0.440). Conclusion: The results of our meta-analysis suggests that vitamin E has a beneficial effect on the incidence and symptoms of CIPN. However, routine prophylactic use of vitamin E is still not recommended. Moreover, more high-quality double-blind RCTs are needed to further validate the effects of vitamin E in prevention of CIPN.